Advanced Fault Diagnosis and Health Monitoring Techniques for Complex Engineering Systems - Li, Yongbo; Li, Bing; Ji, Jinchen; Kalhori, Hamed (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Over the last few decades, the field of fault diagnostics and structural health management has been experiencing rapid developments. The reliability, availability, and safety of engineering systems can be significantly improved by implementing multifaceted strategies of in situ diagnostics and prognostics. With the development of intelligence algorithms, smart sensors, and advanced data collection and modeling techniques, this challenging research area has been receiving ever-increasing attention in both fundamental research and engineering applications. This has been strongly supported by the extensive applications ranging from aerospace, automotive, transport, manufacturing, and processing industries to defense and infrastructure industries.